The Role of Gamification in Teaching Vocabulary to Secondary School Students - Sabirova Gulnoza; Baratova Mohiniso (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This paper explores the effectiveness of gamification as an instructional strategy for teaching vocabulary to secondary school students. In modern education, there is a growing need for innovative methods that enhance learner engagement and promote long-term vocabulary retention beyond traditional memorization-based approaches. Gamification enables teachers to increase students' motivation, activate classroom participation, and support effective vocabulary acquisition. The paper analyzes the advantages, practical application, and impact of gamification on secondary school learners' motivation in English vocabulary learning.